Critical Pedagogy and Dialogic Learning in Classical Islamic Boarding Schools: An Analysis of Discussion Practices in Madrasah Diniyyah Al-Munawwir Krapyak - Radino, Radino; Mubarok, Muhammad Husni (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to explore how discussion-based learning practices (musyawarah) in classical Islamic educational institutions reflect the principles of critical pedagogy and dialogical learning. It analyzes the structure, procedures, and educational outcomes of the discussion method implemented at Madrasah Diniyyah Salafiyyah IV, Pondok Pesantren Al-Munawwir Krapyak, and interprets how these practices cultivate critical consciousness (conscientização), dialogical interaction, and the empowerment of learners (santri). Design/methods/approach – This research employs a qualitative field approach using purposive sampling techniques involving curriculum administrators, the head of the institution, and ten students (santri) from each class level. Data validity was tested through source and technique triangulation, while data analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing. Findings – The findings of this study reveal that: (1) The structure of the discussion method includes dialogical roles such as rais, musharrif, katib, shohibul masalah, formulators, discussion participants (musyawirin), and reviewers (mushahhih); (2) The implementation procedure consists of text reading, issue discussion, and validation of results; (3) This dialogical process not only enhances understanding of Fiqh content and the ability to read classical Islamic texts (kitab kuning), but also develops critical thinking skills, communication abilities, independence, and collective cooperation. These findings align with Freire’s concept of education as a practice of liberation; (4) Challenges such as uneven participation and limited facilitation are addressed through improved coordination, greater involvement of teachers (ustadz), and more systematic lesson planning. Research implications/limitations – This study extends the application of Paulo Freire’s critical pedagogy theory within the context of classical Islamic education, particularly in pesantren. . Originality/value – This study interprets pesantren discussion practices through the lens of critical pedagogy, positioning them as dialogical spaces that foster reflective consciousness and intellectual liberation.